Technological change and earnings inequality in the U.S.: Implications for optimal taxation - Pedro Brinca; Jo\~ao Duarte; Hans A. Holter; Jo\~ao G. Oliveira (University of Oslo, Department of Economics, 2023)
Since 1980, there has been a steady increase in earnings inequality alongside rapid technological growth in the U.S. economy. To what extent does technological change explain the observed increase in earnings dispersion? How does it affect the optimal progressivity of the tax system? To answer these questions, we develop an incomplete markets model with occupational choice. We estimate an aggregate production function with capital-occupation complementarity and four occupations that differ with respect to cognitive complexity and routine task intensity. We calibrate our model to resemble the U.S. economy in 1980 and find that technological transformation can fully account for the increase in earnings dispersion between 1980 and 2015. The main driver is the rising relative wage of non-routine cognitive occupations, which benefit the most from complementarity with capital. Although technological growth is associated with higher earnings inequality, it leads to a significant drop in optimal tax progressivity. Lower progressivity leads to an inflow of workers into higher-paid occupations. This increases output but also raises the wages of the occupations at the bottom of the wage distribution, dampening the redistributive gains from progressive taxation.
Keywords: E21; E23; E62; H21; H23; J24; J31; O33; O40; 330; Earnings Inequality; Taxation; Technological Change; Automation